Health and Wellbeing in Sexual Orientation and Gender Identity - Meads, Catherine (MDPI - Multidisciplinary Digital Publishing Institute, 2020)
This is a collection of published papers from a variety of authors from around the world on the topic of the health and wellbeing of minority sexual orientation and gender identity populations. Some of the included papers focused on health inequality and inequity and some focussed on healthcare delivery. Many showed how health inequities in LGBT+ groups of people were found across a wide variety of political environments and health and wellbeing topics and frequently inadequate healthcare delivery. The increasing interest in research in this area, which has been neglected in the past, shows its growing importance.